АНАЛИЗ ТРАНСМИССИОННОГО МЕХАНИЗМА ДЕНЕЖНО-КРЕДИТНОЙ ПОЛИТИКИ В КАЗАХСТАНЕ - Мухамедиева, А Б (Journal of Economic Research & Business Administration, 2015)
This paper examines monetary policy efficiency in Kazakhstan by investigating the monetary transmission mechanism taking into account canals as interest rate, inflation, money aggregate, credit rate, oil price.